URBAN SOCIETY'S PERCEPTION OF ISLAMIC RELIGIOUS EDUCATION AND ITS IMPLICATIONS FOR CURRICULUM DEVELOPMENT IN THE ERA OF SOCIETY 5.0 - Siti Salwa Md Sawari; Ahmad Muflihin; Warsiyah Warsiyah; Muna Yastuti Madrah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
Based on the Digital Civility Index (DCI), Indonesian internet users have the lowest Digital Civilization Index in Southeast Asia. This phenomenon is evident from the rise of fake news or hoaxes, hate speech, cyberbullying, discrimination, and even fraud. Modernization has also made people's lifestyles more consumptive. Indonesia is also a religious country with the largest Muslim population in the world. Indonesia is ready to face the coming era of what is known as the era of society 5.0. This article analyzes the public perception of urban society in Semarang city of the importance of religious education in their lives and how it is used as an aspect of curriculum development in the era of society 5.0. This research is qualitative research using a method of phenomenology. Data was collected from interviews, observations, and documentation. The results of this study indicate that contextualization of the Islamic religious education curriculum is needed to suit the needs of society in the era of society 5.0. Islamic religious education teaches students the physical dimension (shari'a) and the spiritual dimension (essential) so that Islamic religious education can foster spirituality for urban Muslim communities as a basis for values in everyday behaviour. Islamic religious education must instil the importance of monotheism and ethics in utilizing technology. The era of society 5.0 makes humans the centre (anthropocentric), while Islamic religious education instils the value that God is the centre (theocentric).